Charcot Spine and Parkinson’s Disease - Philippe Loriaut; Sylvie Rozenberg; Patrick Boyer; Benjamin Dallaudière; Frederic Khiami; Elhadi Sariali; Hugues Pascal-Moussellard (Case Reports in Orthopedics, 2014)
Charcot spine is rare condition whose association with Parkinson’s disease (PD) has not been reported yet. The authors reported the cases of two patients with PD who developed Charcot spine. Both patients presented with a history of back pain and bilateral radicular leg pain. They had complete clinical and radiological assessment. Lumbar spine was involved in both patients. Clinical features and response to treatment were described. In the first case, circumferential fusion and stabilization were performed on the dislocated vertebral levels. A solid and stable fusion of the spine was obtained with satisfactory clinical outcome. Surgical treatment has been recommended to the other patient. In both cases, no other neurological etiology was found to account for Charcot spine. In conclusion, Charcot spine is associated with several neurological affections but has not previously been reported in association with Parkinson’s disease.